Dynamics Simulation and Fatigue Life Analysis of Precision Servo Reducer - Liu Xinmeng; Zhang Liyong; Wang Changlu; Yang Huibo (Jixie chuandong)
The characteristic of precision planetary reducer are small size,high precision,small backlash and high stiffness.So it is widely used in robotics,machine tools,medical,military,printing and other industries.But the fatigue failure is easily to occur in precision planetary reduce for its small module,wide speed range and variable load.According to the characteristic of precision servo reducer,the gear dynamic meshing force and fatigue life of planetary gear train are obtained through the dynamics and collaborative simulation.The results show that the sun gear which is the weakness of system can well meet the design requirements.This method which using the dynamic meshing force to analyze the fatigue life of precision servo reducer is more in line with the actual working condition of the reducer.And it can provide the basis for product design and development.